PELATIHAN MEMBUAT GRAFIK DALAM MICROSOFT EXCEL. UNTUK PENGOLAHAN DAN PENYAJIAN DATA - Dwi Setyowati (LPPM IST AKPRIND Yogyakarta, 2019)
A graph is a painting with drawings / lines to determine the ups and downs of a state of existing data. The graph serves to provide data with more interest, can know the ups and downs of a data state, and presents data that can be more easily understood. Diagram is a picture to show or explain a data that will be presented. Diagrams function to make it easier to detail the data that contains numbers. Diagrams are used to summarize and shorten information in every presentation or other matter. Knowing the functions of charts/charts used in processing and presenting data that is changing Layout and Style and Type of Chart/Chart Adding Title, Adding and Removing Data Labels, Changing Scale on the axis of category (x): Filtering and how to Draw Pieces of Chart/Chart Pie.The results achieved from this activity, is that trainees can get to know and use Microsoft Excel to process and present data in graphical form.